What caused the decline in child arrests in England and Wales: The Howard League’s programme or something else? - Farrell, Graham (Crime prevention and community safety, 2019)
There has been a steep decline in child arrests in recent years. The Howard League Research Briefing Child Arrests in England and Wales 2017 attributes this to a Howard League programme of work with police. We show the decline in arrests began well before that programme of work, and conclude the Research Briefing’s claims are unfounded. However, there is strong evidence that the decline in arrests is due to the long-term fall in child offending rates, probably caused by security improvements. While we are sympathetic to the aims of the Howard League, if security is having such positive effects in terms of safer communities and fewer children being processed through the criminal justice system, then it should command wide support.